Adapting Yorùbá Epistemology in Educational Theory and Practice in Nigeria - Oluwatoyin Vincent Adepoju (Yoruba Studies Review)
What is the value of Yoruba epistemology, theory of knowledge, particularly its philosophy of perception, to humanity in general, and to contemporary Nigeria, in particular? How does Yorùbá epistemology connect with educational theory and practice in Nigeria? This essay recognizes but goes beyond the more general overviews on classical Yoruba education and its contemporary significance represented in works of Yorùbá and Africanist scholars. I demonstrate the significance of Yoruba philosophy of education beyond its cultural context, by projecting its universal and timeless value, foregrounding its distinctive concepts in dialogue with ideas from other cultures. In its engagement with Nigerian educational dynamics, the essay concentrates, first, on Yoruba epistemology in its intersection with ethical and metaphysical perspectives from Yoruba thought. Second, the essay deploys the African art-centered investigations of the role of the senses in relating with art, understood as paradigmatic of navigating the world.